UPAYA PENCEGAHAN OBESITAS DENGAN SKRINING IMT DAN GAYA HIDUP SEDENTARI DEWASA MUDA DI PEKOJAN JAKARTA BARAT - Lontoh, Susy Olivia; Dwi Putra, Muhammad Dzakwan; Razaan, Muhammad Naufal (Jurnal Serina Abdimas, 2024)
Obesity and a sedentary lifestyle are health challenges in Indonesian society. Sedentary behavior often occurs in urban areas, especially young adults. The impact of a sedentary lifestyle has a negative impact on health and requires lifestyle improvements and physical inactivity is a risk factor for obesity. The aim of this activity is to increase awareness to prevent obesity and sedentary behavior among educational participants. The method of implementing the activity is screening for blood pressure, BMI, physical activity level and direct education regarding BMI results, physical activity level, the importance of walking and physical activity. The targets of health education activities related to obesity and physical activity are young adults in the Pekojan area, West Jakarta. Educational activities to increase awareness to prevent obesity and sedentary behavior were held on Friday 10 November 2023 at 15.00-18.30. The results of the service activities were attended by 26 participants with 7 male participants and 19 female participants. Based on BMI criteria, there were 20 participants with overweight and obese nutritional status. There were 9 participants who regularly exercised and had light activities and 17 did not regularly exercise and had light activities. To measure the sedentary lifestyle, 11 participants can see how long they sit in a day to watch and use social media and computers (in addition to work or study activities) > 7 hours, so the lifestyle of most of the participants is high sedentary.